Biofermentation of Wheat Bran by Monascus anka and Production of High Value-Added Dietary Fiber - Xuefeng Wu; Siqi He; Hongyi Xu; Hui Zhang; Jing Cai; Min Zhang; Dongdong Mu; Zhenhong Li; Xingjiang Li; Lanhua Liu (Fermentation)
In this study, wheat bran was used to prepare dietary fiber by Monascus anka in liquid fermentation. The structural and functional characteristics of wheat bran dietary fiber were analyzed. Scanning electron microscopy and X-ray diffraction analysis indicated that the insoluble dietary fiber matrix was disrupted during the liquid fermentation. Infrared spectroscopy and differential scanning calorimetry analysis demonstrated that intramolecular hydrogen bonds were broken and the oligosaccharides increased. The soluble dietary fiber content increased from 10.7 g/100 g to 16.5 g/100 g, which contributed to improvements in the water-holding capacity, oil-holding capacity, and swelling capacity of wheat bran dietary fiber. UV–Vis spectroscopy analysis demonstrated that the M. anka wheat bran fermentation broth (MWFB) mainly contained yellow pigments (236.6 μ mL−1). HPLC-MS spectrometry further showed MWFB contained three known Monascus pigments: monasine (observed. m/z 359.1853 [M+H]+), ankaflavin (observed. m/z 387.2151 [M+H]+), and monascorubrin (observed. m/z 382.2007 [M+H]+). In conclusion, M. anka can make the most use of wheat bran and improve the structure and function of dietary fiber, thereby expanding its application potential in functional food additives, gut microbiota modulation, and low-calorie baked goods.